Patterns of participation restriction among older adults at risk of falls and relationship with intrinsic capacity: A latent cluster analysis - Merchant, Reshma Aziz; Chan, Yiong Huak; Aprahamian, Ivan; Morley, John E. (Frontiers in Medicine, 2022)
The concept of participation restriction was first described by the World Health Organization in 2001 as a component of The International Classification of Functioning, Disability and Health Framework. Both falls and fear of falling (FOF) are associated with social isolation, depression, anxiety, poor quality of life and cognitive impairment resulting in participation restriction. Life-space mobility (LSM) is an important indicator for participation restriction which depends on multiple inter-related factors. We aimed to determine participation patterns using latent cluster analysis (LCA) in older adults at risk of falls, its relationship with intrinsic capacity (IC) and its risk prediction. Cross-sectional study of 154 community dwelling older adults ≥ 60 years with falls or risk of falls was conducted. Questionnaires were administered on demographics, hearing, LSM, frailty (FRAIL scale), anorexia of aging (SNAQ), cognition (Montreal Cognitive Assessment, MoCA), FOF (Falls Efficacy Scale-International), physical function, and assessment for handgrip strength (HGS), gait speed, 5-times sit to stand (STS), vision and times-up-and-go (TUG) were performed. Six IC domains (vision and hearing, cognition, nutrition, mobility and depression) were measured. Three pattern of participation cluster were identified, high (n=63, 40.9%), moderate (n=83, 53.9%) and low (n=8, 5.2%). Individuals in the high participation cluster were significantly younger, had higher LSM scores and lower FES-I scores, more robust, fewer ADL and IADL limitations, lower prevalence of low HGS, higher gait speed and shorter TUG. In the fully adjusted model compared to the high participation class, moderate participation was significantly associated with low MoCA scores (OR 4.2, 95% CI 1.7-10.4, p=0.02), poor STS (OR 7.1, 95% CI 3.0-17.0, p=<0.001) whereas low participation was associated with anorexia of aging (OR 9.9, 95% CI 1.6-60.9, p=0.014), poor STS (OR 19.1, 95% CI 2.0-187.5, p=0.011) and hearing impairment (OR 9.8, 95% CI 1.4-70.8, p=0.024). Participants with 3 out of 6 IC decline had a probability of greater than 80% to belong to the low/moderate participation class. Physical function, cognition, hearing and nutrition were significantly associated with low and/or moderate participation class. Future studies are needed to evaluate improvement in participation of those with falls or at risk for falls through restoration of IC.